Trade-off Anak Adat Status as a High-cost of Political Transaction in Papua Local Elections - Dewi, Rosita; Widyatmoko, Bondan (Ministry of Home Affairs, 2024)
Currently, the political transaction through trade-off anak adat (customary child) status is wider applied in Papua local election. Benefiting from the direct elections, the elites competed for political power in the regions by mobilizing ethno-religious sentiments and utilizing money-politics. The voters, in return, behave as clients as they seek to gain material benefits from their preferred candidates in exchange for political loyalty. This condition caused the high-cost politics during the local election. Based on this problem, this paper attempts to analyze the hijacking of adat (customs) through trade-off anak adat status as a form of political transaction which impacted to high-cost politics. This study cultivates the theory of political transactions to analyze the political transaction in Papua local election especially in the gubernatorial election 2018 and election of DPRD (Regional Representative Council)’s member in 2019. This form of political transaction has caused the high-cost of local election in Papua, which is not only in the form of money, but also carried the social cultural high-cost impact. Of course, vote buying will make the candidates have to spend a lot of money. The trade-off of anak adat status from other than Papuan through buying and selling mechanism rather than using achievement and acknowledgement from the adat community would harm the Papuans. Moreover, this practice has brought detrimental destruction to the socio-cultural values of Papuan adat community. This study is qualitative research that use political approach to observe the local election processes in Papua. We used the criteria of credibility and confirmability to validate the data in our qualitative research.